OsIDD2, a zinc finger and INDETERMINATE DOMAIN protein, regulates secondary cell wall formation. Issue 2 (1st August 2017) - Huang, Peng; Yoshida, Hideki; Yano, Kenji; Kinoshita, Shunsuke; Kawai, Kyosuke; Koketsu, Eriko; Hattori, Masako; Takehara, Sayaka; Huang, Ji; Hirano, Ko; Ordonio, Reynante Lacsamana; Matsuoka, Makoto; et al.
Abstract: Previously, we found 123 transcription factors (TFs) as candidate regulators of secondary cell wall (SCW) formation in rice by using phylogenetic and co‐expression network analyses. Among them, we examined in this work the role of OsIDD2, a zinc finger and indeterminate domain (IDD) family TF. Its overexpressors showed dwarfism, fragile leaves, and decreased lignin content, which are typical phenotypes of plants defective in SCW formation, whereas its knockout plants showed slightly increased lignin content. The RNA‐seq and quantitative reverse transcription polymerase chain reaction analyses confirmed that some lignin biosynthetic genes were downregulated in the OsIDD2‐overexpressing plants, and revealed the same case for other genes involved in cellulose synthesis and sucrose metabolism. The transient expression assay using rice protoplasts revealed that OsIDD2 negatively regulates the transcription of genes involved in lignin biosynthesis, cinnamyl alcohol dehydrogenase 2 and 3 ( CAD2 and 3 ), and sucrose metabolism, sucrose synthase 5 ( SUS5 ), whereas an AlphaScreen assay, which can detect the interaction between TFs and their target DNA sequences, directly confirmed the interaction between OsIDD2 and the target sequences located in the promoter regions of CAD2 and CAD3 . Based on these observations, we conclude that OsIDD2 is negatively involved in SCW formation and other biological events by downregulating its target genes. Abstract : Secondary cell wall, which plants make after maturing to reinforce the primary cell wall, is known to be under control of several transcription factors. We added a member of the indeterminate domain family, OsIDD2, to the list of the factors as a negative regulator of lignin biosynthesis in rice.